The Relationship Between Health Locus of Control and Medication Adherence in Hypertensive Patients - Setianingsih, Endah; Herman, Herman; Budiharto, Ichsan (Universitas Tanjungpura, 2024)
Background: Hypertension is a chronic condition that poses significant health risks if not properly managed. Adherence to antihypertensive medication is essential for controlling blood pressure and preventing complications. Health locus of control, which reflects an individual